The Impact of QRIS on MSME Growth in Indonesia: A Strategic Framework for Digital Transformation - Diniar Putri Santosa (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines how the implementation of the Quick Response Code Indonesian Standard (QRIS) influences the growth and financial practices of micro, small, and medium enterprises (MSMEs) in Indonesia. Although QRIS has been widely promoted as a unified digital payment solution that can reduce reliance on cash and enhance transparency, its adoption among MSMEs remains uneven due to gaps in digital literacy, infrastructure limitations, and concerns about data security. To address these issues, this research employs a systematic literature review (SLR) of 20 peer-reviewed articles published between 2020 and 2025. The review was conducted through a structured process involving keyword identification, database searches, screening based on predefined inclusion and exclusion criteria, and thematic synthesis of the selected studies. The findings show that QRIS offers clear benefits in improving transaction speed, operational efficiency, and accuracy of financial records, which collectively support business growth and expand market reach. At the same time, adoption is strongly shaped by perceived usefulness, ease of use, and the influence of customers and peers. The review also highlights persistent barriers, particularly low digital readiness and sensitivity to transaction fees among micro-merchants. Based on the synthesized evidence, this study proposes a strategic framework consisting of digital literacy enhancement, infrastructure support, and strengthened data protection as key pillars for accelerating adoption. The results provide practical insights for policymakers and financial institutions in fostering a more inclusive and sustainable digital payment ecosystem for MSMEs in Indonesia.